Nationalist-Islamist Party in a Liberal Ecosystem: The Solidity and Campaign Strategy of the Prosperous Justice Party (PKS) during the 2014 and 2019 Elections - Al-Hamdi, Ridho (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
This paper examines the nationalist-Islamist party’s solidity and campaign strategy, the Prosperous Justice Party (PKS), in coping with the legislative election under an Open List Proportional Representation (OLPR) system, mainly during the 2014 and 2019 elections. The party solidity is measured by a fourfold indicator: procedural leadership in the decision-making process, conflict resolution mechanism, systematic candidateship, and the commitment upon the values/ideology. In the meantime, the campaign strategy is assessed by four indicators of marketing-mix: product, price, place, and promotion. The finding demonstrates that PKS can maintain the party solidity despite addressing the internal turmoil, mainly related to beef bribery committed by the PKS president in the early of 2013. Furthermore, although PKS executes all campaign strategies in dealing with the 2019 legislative election, the most effective strategy for increasing the PKS’ vote is product and place. The party has a specific platform and strong candidate characteristics. Indeed, it is supported by the loyalty of legislative candidates, cadres, members, and sympathizers who have significant contributions as the vote-getters in mobilizing the electorate. Those proofs indicate that the ideological party can adjust itself in the electoral competition under the liberal system of open-list proportional representation applied by Indonesia. PKS is a good case with its pragmatic strategies.